Legal Frameworks for AI in National Security: Balancing Innovation, Ethics, and Regulation - Upadhayay, Yogita; Sharma, Rituja (Journal of Neonatal Surgery, 2025)
The incorporation of sophisticated technologies into national security operations offers both advantages and obstacles. Although these advances improve defense capabilities, intelligence collection, and threat identification, they simultaneously provoke issues about ethics, accountability, and regulatory supervision. The legal and governance frameworks necessary for responsible implementation while addressing dangers such as bias, mass surveillance, and autonomous warfare. Primary focal points encompass the enhancement of legislative frameworks, the creation of autonomous oversight bodies, the cultivation of public-private partnerships, and the advancement of international collaboration to ensure that security measures adhere to human rights and ethical principles. As technology progress surpasses current rules, governments must implement flexible policies that reconcile security requirements with civil freedoms. The importance of interdisciplinary collaboration is highlighted to guarantee that governance strategies incorporate both technical and ethical factors. By emphasizing openness, accountability, and ethical adherence, policymakers can establish a sustainable governance framework that preserves national security while respecting democratic principles. The imperative for proactive regulatory frameworks and international collaboration to avert misuse and promote responsible innovation.